Chapter VI.1 Cross-communal scholarly interactions - Gibson, Nathan P. (Taylor & Francis, 2022)
This chapter traces cross-communal interactions in the fields of medicine, mathematics and what the historical actors called the natural sciences. It discusses various modern interpretations of those interactions and engages with a number of historical problems researchers face when studying the extant sources. After a substantive survey of the current state of research, the chapter addresses four areas which offer fascinating evidence for interactions between scholars adhering to different faith communities: textual practices; teaching; patronage; workplaces. The chapter ends by suggesting future research directions.